Comment: Characterization of Two Historic Smallpox Specimens from a Czech Museum - Porter, Ashleigh F; Duggan, Ana T; Poinar, Hendrik N; Holmes, Edward C (Viruses, 2017)
The complete genome sequences of two strains of variola virus (VARV) sampled from human smallpox specimens present in the Czech National Museum, Prague, were recently determined, with one of the sequences estimated to date to the mid-19th century. Using molecular clock methods, the authors of this study go on to infer that the currently available strains of VARV share an older common ancestor, at around 1350 AD, than some recent estimates based on other archival human samples. Herein, we show that the two Czech strains exhibit anomalous branch lengths given their proposed age, and by assuming a constant rate of evolutionary change across the rest of the VARV phylogeny estimate that their true age in fact lies between 1918 and 1937. We therefore suggest that the age of the common ancestor of currently available VARV genomes most likely dates to late 16th and early 17th centuries and not ~1350 AD.
Keywords: genom virový; Česká republika; virus varioly; Phylogeny; pravé neštovice; lidé; Genome, Viral; Smallpox; fylogeneze; Variola virus; Museums; Czech Republic; muzea; Evolution, Molecular; molekulární evoluce; Humans